PERANCANGAN WEBSITE PEMESANAN TRAVEL ONLINE PADA PT NETRAL LINTAS NUSANTARA - Fitri, Nabila Aura; Amelia, Nabila; Zain, Nayla; Hikmal, Hikmal; Pragani, Saydripo (JURNAL ILMIAH INFORMATIKA, 2025)
As work to the literature, it uses design and development of the long distance online web-based ticketing system on PT Netral Lintas Nusantara as inter city land transportation with based on Pekanbaru, Riau. There are problems inherent from the current manual ticketing system among which are slow ticketing process to the services, high chances of human errors to the data entry and limited reach of the customer service. The main objective of this study is to develop computerized booking and ticketing system on-line that will minimize of ticketing and booking and expose brethren in Christ, to global network, such that there would be access to airports with investment in the international and local and international airline and flight, which users can upload the softcopy of card to board their flight. Discretion is also designed to solve the existing system inadequacies through system requirement analysis, database design and website development method. The antinicipated output of the design is a remarkable performance enhancement of PT Netral Netral Lintas Nusantara's operational system, 24/7 service expansion in real time to customers, and an enormous administration manual usage reduction. In this information age, the official launching of the website is a key action in modernising services that enables the company to enhance competitiveness on the digital platform.